Edukasi Membudayakan Masyarakat Mengkonsusmsi Sayur Bayam Melalui Pengolahan Kripik Di Kampung Parang Kelurahan Tamaanrea Jaya Makassar - Arifin, Nurbaeti; Amelia, A. Rizki; Haeruddin (Window of Community Dedication Journal, 2020)
Not many people have processed spinach-based chips know, because the residents know that spinach can only be processed into vegetables only. Consuming spinach is very good for the health of the body, because spinach contains vitamins and minerals that are quite omplete. The results of this activity are, (1) Increasing public knowledge (majelis ta'lim) regarding the benefits of spinach and spinach chips processing (2) Open job opportunities for housewives as additional income.